Strategi Pemasaran Pakan Ikan Buatan Berbahan Baku Lokal Daun Kelor Di Gampong Reuleut Timur Kecamatan Muara Batu - Riani Riani; Rachmawati Rusydi; Mainisa Mainisa; Salamah Salamah; Saiful Adhar (Jurnal Pengabdian Masyarakat: Darma Bakti Teuku Umar, 2022)
Moringa leaf-based fish feed is feed that is processed by pond farmers in Gampong Reuleut Timur, Muara Batu District, North Aceh, using Moringa leaf raw materials that have good nutritional content and are in accordance with fish needs. This feed is relatively cheap with protein content that meets the needs of fish. However, the feed has not been able to reach a wide market. This is due to the lack of knowledge of farmers about marketing strategies. The service team, through community service activities, aims to provide counseling about marketing strategies for artificial fish feed. Service activities were carried out in Gampong Reuleut Timur, Muara Batu District, North Aceh Regency. Extension activities were carried out by presenting material on the 4P marketing strategy, namely product, price, place, and promotion, and distributing questionnaires to participants to evaluate their understanding of the material. The result of this activity is the increased understanding and knowledge of partners about the 4P marketing strategy, with the hope that later it will be applied to the business that has been occupied in order to obtain maximum profit.<img src="data:image/png;base64,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